The Effect Of STEM-Based Project-Based Learning In Improving High School Students' Visual Mathematical Ability - Sari, Rika Mulyati Mustika; Sopiany, Hanifah (SJME (Supremum Journal of Mathematics Education), 2023)
This research is based on the problem of the low mathematical visual thinking ability in learning mathematics. To overcome this, research was carried out using a STEM-based Project-Based Learning (PjBL-STEM) model. This study examines the problem of improving visual mathematical abilities among students who receive mathematics learning with the STEM-based Project-Based Learning (PjBL-STEM) model. This research is quasi-experimental, the design used is the Nonequivalent Control Group Design using the Purposive Sampling technique. The population in this study were high school students in Bandung Regency in the academic year 2021/2022, with the research sample being high school students in class X. The instrument used in the study was a visual mathematical ability test. Data analysis was carried out quantitatively by using the Independent Sample t-test. The results showed that (1) Overall the application of the PjBL-STEM learning model could improve students' mathematical visual thinking abilities, (2) Improved mathematical visual thinking skills of students whose learning using the PjBL-STEM learning model was significantly better than students who learned using conventional learning models.